Towards a Hermeneutic-Phenomenological Methodology for Theology - Horner, Robyn ca. 20./21. Jh. (International journal of practical theology, 2018)
The question of methodology in theology is sometimes vexed. In this article I seek to offer a hermeneutic phenomenological methodology for theology, utilising the insights of recent French phenomenology. Such a methodology demands that we refrain from making judgments in advance about the kinds of phenomena it is possible to encounter. Not only does this enable us to re-frame questions about the distinctions between philosophy and theology, but it also frees theologians from the problematic requirement of assuming a methodological atheism, particularly as they undertake practical theological research.